THE EFFECT OF ACCREDITATION ON THE INSTITUTIONAL PERFORMANCE OF THE PRIVATE HIGHER EDUCATION INSTITUTIONS IN OMAN - Abdullah, Alkindi Badar Saif; Salleh, Mad Ithnin (Veredas do Direito, 2026)
This study investigates how accreditation affects governance, management, and stakeholder perceptions of private colleges and universities in Oman. Data was collected from 351 academic and administrative staff using stratified random sampling in a quantitative cross-sectional design. The survey found that most respondents view accreditation positively (mean = 4.15, SD = 0.53). They say accreditation requires openness, responsibility, stakeholder involvement, and continuous improvement. Accredited institutions must be accountable and constantly improve, which can lead to enhanced educational quality and better student outcomes. The regression analysis shows that accreditation is a significant predictor of institutional performance (β = 0.692, p < 0.001), accounting for 47.1% of the outcomes. These findings strongly suggest that accreditation enhances the quality of private higher education in Oman. The study elucidates the ways in which accreditation strengthens emerging higher education systems, thereby enriching theoretical understanding. Furthermore, the results provide policymakers with evidence-based recommendations for using accreditation to enhance governance and institutional effectiveness. While the cross-sectional design limits the ability to draw causal inferences, it establishes a robust foundation for future longitudinal studies in Oman and the Gulf region, which could further investigate the long-term effects of accreditation on higher education systems in these areas.